Analysis of a new stabilized finite volume element method based on multiscale enrichment for the Navier-Stokes problem. Issue 8 (7th November 2016) - Wen, Juan; He, Yinnian; Zhao, Xin
Abstract : Purpose: The purpose of this paper is to propose a new stabilized finite volume element method for the Navier-Stokes problem. Design/methodology/approach: This new method is based on the multiscale enrichment and uses the lowest equal order finite element pairs P 1 / P 1 . Findings: The stability and convergence of the optimal order in H 1 -norm for velocity and L 2 -norm for pressure are obtained. Originality/value: Using a dual problem for the Navier-Stokes problem, the convergence of the optimal order in L 2 -norm for the velocity is obtained. Finally, numerical example confirms the theory analysis and validates the effectiveness of this new method.